Parallel Descriptions of Ilokano and English Personal Pronouns: A Contrastive Analysis - R. Caangay, Ria Bianca; J. Ponce, Mary Rose (Researchparks Publishing, 2023)
Personal pronouns are among the simplest grammatical features of the English language; however, learners still struggle translating this language unit from Ilokano to English. This study thus examined the structure, meanings, and usage of personal pronouns in both Ilokano and English languages as well as the contrastive structure in these two languages. This study employed a qualitative research design using contrastive analysis. The data used was from a qualified informant who confirmed the categorization of personal pronouns obtained from credible sources. Results showed that the two languages vary in terms of function, form and distribution depending on their social and linguistic environment. Their use of the personal pronouns also indicates a difference in the formality of language where Ilokano uses plural form in a formal conversation while the English language remains definite despite its formality. This result implies a contribution in the development of contextualized linguistic materials for Ilokano personal pronouns.